Activation of 4-Hydroxycinnamate Hydroxylase in Extracts from Sorghum - Stafford, Helen A. (1974)
Three types of activation of 4-hydroxycinnamate hydroxylase have been observed in extracts of Sorghum bicolor. One involves the elimination of a lag period either by increasing the enzyme concentration or by the addition of a catalytic amount of caffeic acid. Two involve increases after freezing of incubation mixtures containing both hydroxycinnamate and ascorbate, one being a rapid but short-lived increase that may be limited to the freeze-thaw period, the other a slower and more sustained effect on the maximum linear rate obtained during the incubation period after thawing.